2010
DOI: 10.2147/copd.s14063
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association of ischemic heart disease with COPD when taking into account classical cardiovascular risk factors

Abstract: The aim of our study is to determine whether chronic obstructive pulmonary disease (COPD) is an independent risk factor for ischemic heart disease and whether this association is related with a greater prevalence of classical cardiovascular risk factors. Ours is a case-control cross-sectional study design. Cases were hospital patients with ischemic heart disease in stable phase, compared with control hospital patients. All patients underwent post-bronchodilator (PBD) spirometry, a standardized questionnaire, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 38 publications
(38 reference statements)
1
11
0
Order By: Relevance
“…The negative association between dyslipidemia and COPD in our population might be also due to the mild severity of airway obstruction in our subjects or/and due to racial/ethnic differences (10). …”
Section: Discussionmentioning
confidence: 82%
“…The negative association between dyslipidemia and COPD in our population might be also due to the mild severity of airway obstruction in our subjects or/and due to racial/ethnic differences (10). …”
Section: Discussionmentioning
confidence: 82%
“…Actually, COPD might be an independent risk factor for CVD[ 2 4 , 24 26 ]. However, some studies have failed to confirm the association between COPD and CVD, and some authors have suggested that this association might be explained by the presence of shared risk factors [ 5 ]. One strong point of our investigation is that study subjects were matched regarding age, sex and smoking history, variables that influence differences in cardiovascular mortality.…”
Section: Discussionmentioning
confidence: 99%
“…However, shared risk factors (age, sex, smoking, low physical activity), might also explain the association between COPD and CVD. In fact, some studies did not find a clear connection between CVD and COPD when classical cardiovascular risk factors were taken into account [ 5 , 6 ]. Underuse of cardiac medications, especially beta-blockers, in COPD might explain the higher risk of cardiovascular events in this population [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…This, however, is due to the ageing of patients, since, once age had been controlled for, prevalence did not prove very different to what might have been expected (Table 4). This finding indicates that, when studying the association between COPD and cardiovascular diseases, the confounding role of risk factors must be taken into account [33]. …”
Section: Discussionmentioning
confidence: 99%